2001
DOI: 10.1046/j.1525-1497.2001.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Managed Care, Professional Autonomy, and Income. Effects on Physician Career Satisfaction

Abstract: CONTEXT: Career satisfaction among physicians is a topic of importance to physicians in practice, physicians in training, health system administrators, physician organization executives, and consumers. The level of career satisfaction derived by physicians from their work is a basic yet essential element in the functioning of the health care system. OBJECTIVE: To examine the degree to which professional autonomy, compensation, and managed care are determinants of career satisfaction among physicians. DESIGN:Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
103
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 17 publications
6
103
1
3
Order By: Relevance
“…6,7 Two recent literature reviews concluded that the factors most strongly associated with physician well-being include work environment (e.g., work hours, income), [19][20][21] physician autonomy (e.g., control over work, ability to provide needed service), 7,19,22 and changes in the local market (e.g., managed care). 22,23 Intrinsic motivating factors have received relatively scant attention because medical educators and practitioners have thought it too difficult to design institutional strategies and interventions that address stable physician characteristics. [24][25][26] Instead policymakers have tended to focus on extrinsic factors that are more readily manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Two recent literature reviews concluded that the factors most strongly associated with physician well-being include work environment (e.g., work hours, income), [19][20][21] physician autonomy (e.g., control over work, ability to provide needed service), 7,19,22 and changes in the local market (e.g., managed care). 22,23 Intrinsic motivating factors have received relatively scant attention because medical educators and practitioners have thought it too difficult to design institutional strategies and interventions that address stable physician characteristics. [24][25][26] Instead policymakers have tended to focus on extrinsic factors that are more readily manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…10 Findings from this study have shown that physician satisfaction and dissatisfaction vary across region, specialty, age, and income, 11 and that being in a small or solo practice is associated with dissatisfaction. 12,13 Further, Stoddard and his colleagues 14 found that the most important determinants of satisfaction with a career in medicine were autonomy and professional values such as altruism, the maintenance of high ethical standards, a commitment to the needs of society, and humanistic values such as empathy, integrity, and trustworthiness. Landon and his colleagues 15 studied changes in physician satisfaction between 1997 and 2001.…”
mentioning
confidence: 99%
“…In fact, since a lack of professional and clinical autonomy is associated with career dissatisfaction [29] and poor professional rewards [30] , the findings indicate that alternative payment schemes, both blended forms and pure APP, do not threaten physicians' clinical autonomy. Moreover, the intrinsic and unalterable tensions of practicing medicine are not affected by alternative payment methods.…”
Section: Discussionmentioning
confidence: 98%